Perancangan Health Risk Assessment untuk Meminimalkan Penyakit Akibat Kerja pada Departemen Boiler Perusahaan Makanan di Surabaya - Elizabeth Paula; Herri Christian Palit (Jurnal Titra, 2020)
Occupational health is an important aspect to be considered by company. Workers, while producing food, cannot be separated from risk of getting occupational diseases. This company wants to implement ‘Zero Diseases’ program and requires documented monitoring and relevant control methods for occupational diseases arising from work activities. Assessing a Health Risk Assessment might be considered the most appropriate way to answer the company’s need related to documenting types, risks categories, and appropriate control methods of related occupational diseases. The method used in data collection is direct interviews, questionnaires, and annual employee’s health monitoring data from the company. The data is processed according to the needs of each type of occupational diseases. The risk categories are grouped based on a risk matrix. Sums up low risk occupational diseases as much as 59%, medium risk as much as 37%, and high risk as much as 4%. Control methods are included and adjusted to the types of occupational diseases and based on the principal of hierarchy of controls. All types of occupational diseases have administrative controls, eight of them have Personal Protective Equipmemt (PPE), and one of them has engineering controls.